A matter of time: how musical training affects time perception - Mittal, Jahanvi; Juneja, Khushi Kaur; Saumya, Saumya; Shukla, Anuj (Frontiers in Neuroscience, 2024)
Musical training has been linked to changes in early attentional and perceptual processing. Thus, such an altered attentional and perceptual processing has enabled musicians to judge the duration differently than non-musicians. Although these claims seem intriguing, there are many questions that are not addressed yet, for example, how would the performance of musically-trained differ from that of untrained on visual and auditory temporal judgments? Is there any advantage to musically-trained person in temporal processing? To understand these questions, we thus conducted a series of auditory and visual temporal bisection tasks on 32 musically-trained and 32 musically-untrained participants. We hypothesized that if music training modulates general sensitivity to temporal dimensions, then the temporal judgments of musically-trained participants would differ from those of untrained participants in both visual and auditory tasks. Each participant performed a total of 140 trials (70 visual and 70 auditory) in two different blocks. For each participant, a Point of Subjective Equality (PSE) was obtained for visual and auditory conditions.The findings revealed a significant modality effect on time perception, with auditory stimuli being consistently overestimated compared to visual stimuli. Surprisingly, the musically-trained group exhibited a tendency to underestimate duration relative to the Musically-untrained participants.Although these results may appear counterintuitive at first glance, a detailed analysis indicates that the length of musical training plays a significant role in modulating temporal processing within the musically-trained group.